Ethnographic Descriptions of “Land und Leute” in the Alps-Adriatic Region in the 19th Century - Fikfak, Jurij; Schönberger, Klaus (Traditiones, 2024)
Ethnographic accounts from the 19th century, including “Land und Leute”, statistical reports and travelogues, provide insight into how ethnographers (broadly defined) presented and investigated the transformations occurring in the multicultural Alps-Adriatic region. An examination of these documents elucidates “in-between” practices among diverse languages and cultures, and facilitates an exploration of how individuals negotiated complex national and cultural identifications.